NOVEL TYAGA WANI MATI KARYA I NYOMAN MANDA PENDEKATAN SOSIOLOGI SASTRA - Defiyanti, Ni Wayan Sintia (Humanis; Volume 6. No. 2. Februari 2014, 2014)
This research study about modern Bali belleslettres which in form of novel with novel title of Tyaga Wani Mati. This Novel of story about war of Badung puputan. Struggle of people and king of Badung Tyaga Wani Mati (militant alertness) fight against grind done by Belanda make this novel draw to be studied. Target of this analysis is to explaining and lay open by mendetail structure developing novel of Tyaga Wani Mati. Besides this analysis also aim to know social aspects implied ining novel of Tyaga Wani Mati. Used theory, that is structural theory and art sociology theory. Used method at this research pass three phase; namely ready phase of data, phase analyse data, and phase presentation of result analyse data. At ready phase of data use observation method and interview supported with record-keeping technique and translation technique. Phase analyse data use method is qualitative assisted with analytic descriptive technique. Phase hereinafter, that is phase presentation of result analyse data use informal method assisted with inductive and deductive technique. Reached result in this research that is laying open narrative structure of novel of Tyaga Wani Mati cover incident, path, figure and figure, background. theme, and commendation. That element by together become one functioning unity develop; build novel story of Tyaga Wani Mati. Despitefully this research also analyse sociology aspect cover; struggle aspect, history aspect / historical, love aspect, faithfulness aspect, and religion aspect.
Keywords: novel, structure, sociology. 1. Latar